2023
DOI: 10.1093/jsxmed/qdac043
|View full text |Cite
|
Sign up to set email alerts
|

Symptoms and associated impact in pre- and postmenopausal women with sexual arousal disorder: a concept elicitation study

Abstract: Background Approximately 26% of adult women in the United States suffer from female sexual arousal disorder (FSAD), yet little has been done to compare the experience of FSAD in pre- and postmenopausal women, which is critical to enhance the current understanding of FSAD and inform the development and assessment of treatment options for these patient populations. Aim To explore the experience of condition-associated symptoms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 15 publications
0
0
0
Order By: Relevance
“…Although the subset population of women randomized to sildenafil cream with either female sexual arousal disorder only or female sexual arousal disorder with concomitant decreased desire did not demonstrate statistically significant decreased sexual distress as measured by the coprimary endpoint of FSDS-DAO question 14 ( P =.95, Table 3 ), which assesses concern about difficulties with sexual arousal, we found that several other FSDS-DAO questions, which asked about generalized feelings related to sexual distress and interpersonal difficulties, showed significant improvement with sildenafil cream compared with placebo cream (questions 3, 5 and 10, all P ≤.04, Table 3 ) in this exploratory subset. The total FSDS-DAO score decreased by about 7 points for sildenafil cream users in the subset population (a clinically meaningful decrease in sexual distress 11 ) compared with a 2-point decrease for placebo cream users ( P =.10).…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…Although the subset population of women randomized to sildenafil cream with either female sexual arousal disorder only or female sexual arousal disorder with concomitant decreased desire did not demonstrate statistically significant decreased sexual distress as measured by the coprimary endpoint of FSDS-DAO question 14 ( P =.95, Table 3 ), which assesses concern about difficulties with sexual arousal, we found that several other FSDS-DAO questions, which asked about generalized feelings related to sexual distress and interpersonal difficulties, showed significant improvement with sildenafil cream compared with placebo cream (questions 3, 5 and 10, all P ≤.04, Table 3 ) in this exploratory subset. The total FSDS-DAO score decreased by about 7 points for sildenafil cream users in the subset population (a clinically meaningful decrease in sexual distress 11 ) compared with a 2-point decrease for placebo cream users ( P =.10).…”
Section: Resultsmentioning
confidence: 90%
“…Before the start of the study, we conducted a qualitative content validity study among women with female sexual arousal disorder to ensure that the efficacy endpoints, which were patient-reported outcome measures, were fit for purpose and valid for this specific population. 11 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Female sexual dysfunction is defined as a disorder, at any stage of the sexual response, that is capable of generating personal stress and having a negative impact on quality of life and interpersonal relationships [3]. Their etiologies are multifactorial and their actual incidence is currently unknown [12]. They are often a taboo subject in our society at different levels and, unsurprisingly, also during clinical interviews [13], which makes self-completion questionnaires such as the FSM an emerging tool to facilitate diagnosis, as they facilitate data collection by allowing the patient to fill them in privately and anonymously [14].…”
Section: Discussionmentioning
confidence: 99%

Sexuality in Postmenopausal Women with Genital Prolapse

Fernández Rísquez,
Carballo García,
Hijona Elósegui
et al. 2023
JCM
“…If positive, it could lead to a new therapeutic area for the unmet treatment needs of premenopausal and postmenopausal women with female sexual arousal disorder. 6,7…”
mentioning
confidence: 99%